2006
DOI: 10.1682/jrrd.2005.06.0103
|View full text |Cite
|
Sign up to set email alerts
|

Motions or muscles? Some behavioral factors underlying robotic assistance of motor recovery

Abstract: Abstract-Robotics and related technologies have begun to realize their promise to improve the delivery of rehabilitation therapy. However, the mechanism by which they enhance recovery remains unclear. Ultimately, recovery depends on biology, yet the details of the recovery process remain largely unknown; a deeper understanding is important to accelerate refinements of robotic therapy or suggest new approaches. Fortunately, robots provide an excellent instrument platform from which to study recovery at the beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
200
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 327 publications
(218 citation statements)
references
References 58 publications
(70 reference statements)
4
200
0
4
Order By: Relevance
“…Evidence from upper limb (UL) studies suggests that physical interaction or interactive training produces the greatest gains in recovery of motor function compared with purely passive or resistive modes [20]; we chose to use a robot for training in part because robots lend themselves to application of ML principles that are now widely accepted as a modern basis for effective rehabilitation. Compared with a human therapist, robots allow for massed repetitive practice of affected limbs and can provide therapists with a variety of practice conditions that can be tailored to the needs of individual patients.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from upper limb (UL) studies suggests that physical interaction or interactive training produces the greatest gains in recovery of motor function compared with purely passive or resistive modes [20]; we chose to use a robot for training in part because robots lend themselves to application of ML principles that are now widely accepted as a modern basis for effective rehabilitation. Compared with a human therapist, robots allow for massed repetitive practice of affected limbs and can provide therapists with a variety of practice conditions that can be tailored to the needs of individual patients.…”
Section: Introductionmentioning
confidence: 99%
“…This plateau is determined by the same problematic clinical tools already discussed. Some authors have suggested that this plateau may actually be the patients consolidating their poststroke practice experience rather than optimal biological recovery [85][86][87] and this, in itself, has important implications in the timing of how we deliver treatment after a stroke.…”
Section: Traditional Approachesmentioning
confidence: 99%
“…En estos casos, se suelen seguir terapias de rehabilitación asistida por robots para estimular la neuroplasticidad (Van Peppen et al 2004). Si la intención de movimiento de los pacientes pudiera extraerse en tiempo real, sería posible controlar los dispositivos de asistencia de una manera más natural de forma que se prestase solo la asistencia requerida, incentivando la participación activa del paciente y, por tanto, maximizando los beneficios de dicha terapia (Hogan et al, 2006). La utilización de la información espacial de mapas de activación mioeléctrica constituye un método novedoso que ya ha demostrado buenos resultados en la identificación de tareas en trabajos previos (Stango et al, 2015), tanto en sujetos sanos comoen pacientes con lesión medular incompleta durante contracciones isométricas (Jordanic, et al, 2016a, b;Rojas-Martínez et al, 2013).…”
Section: Introductionunclassified